2011
DOI: 10.1007/s11418-011-0597-8
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity effect of Tamarindus indica L. pulp aqueous extract in high-fat diet-induced obese rats

Abstract: Obesity and overweight are associated with atherosclerosis, fatty liver, hyperlipemia, diabetes mellitus, and various types of cancer. The global prevalence of overweight and obesity has reached epidemic proportions. Here, we investigated the effect of Tamarindus indica pulp aqueous extract (TIE) in diet-induced obese Sprague-Dawley rats. The animals were divided into five groups and labeled as follows: the normal control (NC) group received normal diet; the positive control (PC) group received high-fat diet; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 28 publications
3
34
0
2
Order By: Relevance
“…It is known to be rich in polyphenolics such as rutin, quercetin, and 1-deoxynojirimycin (DNJ). Therefore, it has been used in traditional medicine to treat several metabolic diseases including dyslipidemia (Azman et al 2012), diabetes (Flores et al 2012), fatty liver disease (Ou et al 2011), and hypertension (Kobayashi et al 2006). The mulberry leaf also enhances antioxidant enzyme activities in diabetic rats (Ha et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is known to be rich in polyphenolics such as rutin, quercetin, and 1-deoxynojirimycin (DNJ). Therefore, it has been used in traditional medicine to treat several metabolic diseases including dyslipidemia (Azman et al 2012), diabetes (Flores et al 2012), fatty liver disease (Ou et al 2011), and hypertension (Kobayashi et al 2006). The mulberry leaf also enhances antioxidant enzyme activities in diabetic rats (Ha et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tamarind pulp water extract has an anti-obesity effect in high fat–induced rats [3] and high carbohydrate–induced rats [16]. Research showed that tamarind pulp water extract decreased LDL levels and triglyceride levels [3].…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that tamarind pulp water extract decreased LDL levels and triglyceride levels [3]. Finna et al showed that tamarind pulp water extract has an anti-obesity effect in a high carbohydrate–induced diet at the dose of 75 mg/kg bw [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is rich in polyphenolic compounds including rutin, quercetin, and 1-deoxynojirimycin (DNJ). Hence, it has been medicated several diseases including dyslipidemia [7], diabetes [8], fatty liver [6], and hypertension diseases [8]. Besides, the mulberry fruits induce enzymatic antioxidant in diabetic models [8].…”
Section: Introductionmentioning
confidence: 99%